2006
DOI: 10.1248/jhs.52.748
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Kalpaamruthaa on Lipid Peroxidation and Antioxidant Status in Experimental Mammary Carcinoma in Rats

Abstract: There has been a growing interest in studying the role played by lipid peroxidation and antioxidant status in breast cancer. Free radicals are found to be involved in both initiation and promotion of multistage carcinogenesis. In the present study, effects of Kalpaamruthaa (KA), a modified Siddha preparation on the levels of lipid peroxides (LPO) and status of antioxidants in several tissues were studied in mammary carcinoma rats. The levels of reactive oxygen species (ROS) were also measured in the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Furthermore, Khanzode and colleagues [41] have also reported that the oxidative stress generated in cancer conditions are due to an imbalance between proxidants and antioxidants status and it seems to play an important role in breast cancer. Moreover, the abnormalities in the status of antioxidants defence system and improper balance between productions of reactive oxygen species have been identified as oxidative stress in various pathological conditions including cancer [42,43]. It is reported that the enzymic and non-enzymic antioxidants are the form of the first line defence mechanism to scavenge excessively generated ROS in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Khanzode and colleagues [41] have also reported that the oxidative stress generated in cancer conditions are due to an imbalance between proxidants and antioxidants status and it seems to play an important role in breast cancer. Moreover, the abnormalities in the status of antioxidants defence system and improper balance between productions of reactive oxygen species have been identified as oxidative stress in various pathological conditions including cancer [42,43]. It is reported that the enzymic and non-enzymic antioxidants are the form of the first line defence mechanism to scavenge excessively generated ROS in the system.…”
Section: Discussionmentioning
confidence: 99%